Manfaat Aktivasi Digitalisasi pada Pendapatan UMKM - Christina, Christina; Putra, Claudio Ravindra; Steven, Leonardo; Aruan, Michelle; Joab, Jonathan; Novianti, Debby; Desia, Wirini; Wangsa, Rivaldo; Rinaningsih, Rinaningsih (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2022)
MSMEs have the potential to achieve economic growth, even distribution and labor income, create jobs, and overcome poverty in Indonesia. Therefore, it is necessary to empower and develop the potential of MSMEs whose perpetrators are recorded to reach 64.2 million and contribute more than half of the gross domestic product in 2021 through the PKM program. One of the biggest obstacles for MSME perpetrator is marketing their products by utilizing digital marketing which has a big impact as the times move towards modernity. So that education is needed on the use of appropriate media to market products from MSME perpetrator. From January to June 2022, in-depth interviews were conducted, it can be seen how much knowledge about digital marketing and based on the results of the interview, appropriate materials are made so that perpetrator can take advantage of technology and can independently develop their businesses. It turns out, perpetrator don't know much about digital marketing, so education is needed, from planning to execution. Through the provision of materials, partners can use social media as a platform to do digital marketing independently and their business can grow rapidly.